An innovative study on a hybridized ship powering system with fuel cells using hydrogen and clean fuel blends. (25th February 2023) - Seyam, Shaimaa; Dincer, Ibrahim; Agelin-Chaab, Martin
Highlights: Five alternative fuels are chosen with different concentrations. Hybrid marine engine produce 27773 kW with an increase of 32 % Hybrid engine has thermal and exergetic efficiency of 29.5% and 38.5%, respectively. Carbon emission is reduced by 61% because of alternative fuel blends. Specific fuel consumption is reduced by an average of 20%. Abstract: Marine transportation is the main means of transporting massive goods overseas that cannot be transported using rail or aviation. Using fossil fuels has significantly impacted global warming and changed the climate. This paper focuses on the development of a new hybridized powering system that uses environmentally benign hydrogen-based fuels in five different blends. The proposed powering system is uniquely designed and consists of an internal combustion engine (ICE), gas turbine (GT), solid oxide fuel cell (SOFC), and thermoelectric generators (TEG). This system is investigated thermodynamically after validating the results with a traditional ICE using marine gas oil (MGO-DMA) fuels. The two traditional ICE engines produce a net power of 21048 kW with a 22.9 % energy efficiency and a 29.0 % exergy efficiency. However, the hybridized GT and ICE system can deliver a maximum power of 27773 kW using a dimethyl-ether and hydrogen fuel blend with a percentage increase of 32 %, while the minimum power is obtained to be 24968 kW (an increase of about 19 %) using methane and hydrogen blend. The addition of SOFC can increase the GT power by double and raise the energy efficiency from 19 % to 32 %. Blending all five fuels, such as hydrogen, methane, dimethyl ether, methanol and ethanol, can drop the specific fuel consumption to 254.5 g/kWh by 21.7 % and raise the total power to 27719.5 by 31.7 %. In addition, the carbon emissions are drastically decreased by about 61 % by utilizing sustainable fuel blends; meanwhile, the overall system performance is increased by more than 35 %.